﻿Updated taxonomy on Gerronema (Porotheleaceae, Agaricales) with three new taxa and one new record from China - Qin Na; Yaping Hu; Hui Zeng; Zhizhong Song; Hui Ding; Xianhao Cheng; Yupeng Ge (MycoKeys, 2022)
Only three Gerronema (Porotheleaceae) species have been previously recorded in China. Here, we report collections of a fourth species in China: G. nemorale Har. Takah., which is widely distributed in Chinese temperate to subtropical zones. We also formally describe three new species, collected from Anhui, Fujian, and Zhejiang provinces: G. baishanzuense sp. nov., G. microcarpum sp. nov., and G. zhujian sp. nov. Furthermore, we include the results of a phylogenetic analysis of Porotheleaceae based on a multi-locus (ITS + nLSU) dataset. The results, which indicate that Gerronema is polyphyletic, support the taxonomic recognition of the three new species. Morphological descriptions, photographs, line drawings, and comparisons with closely related taxa are presented for the new and newly recorded species. A key to the seven species of Gerronema in China is also provided.